The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10689-011-9420-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counseling for patients and families with hereditary breast and ovarian cancer in a developing Asian country: an observational descriptive study

Abstract: Genetic counseling (GC) and genetic testing are vital risk management strategies in hereditary breast and ovarian cancer (HBOC) syndromes. Hitherto, cancer genetic testing amongst Asians has been described only in developed and high-income Asian countries. We studied the uptake and acceptance of GC and genetic testing services to Asian BRCA carriers in a middle-income country. A total of 363 patients were tested by full sequencing and large rearrangement analysis of both BRCA1 and BRCA2 genes in the Malaysian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 29 publications
4
47
0
Order By: Relevance
“…A variety of cost and logistical barriers were endorsed or stated across 15 studies. The financial cost of genetic testing and concerns around future insurability or financial discrimination were often reported (17,24,25,31,37,44,46). The time and travel required to attend an appointment were also stated as barriers (24,28,29,31,33,37,45,47).…”
Section: Barriers To Attendancementioning
confidence: 99%
“…A variety of cost and logistical barriers were endorsed or stated across 15 studies. The financial cost of genetic testing and concerns around future insurability or financial discrimination were often reported (17,24,25,31,37,44,46). The time and travel required to attend an appointment were also stated as barriers (24,28,29,31,33,37,45,47).…”
Section: Barriers To Attendancementioning
confidence: 99%
“…Clinical genetics services are relatively new and underdeveloped and, moreover, our data and data from Asian Americans have shown that risk assessment models for BRCA1 and BRCA2 , which were largely built on families with multiple cancers, underestimate the number of BRCA carriers in Asians compared to Caucasians [12,13]. We have previously found that family history is poorly reported in Asian families in Malaysia, in part due to the stigma associated with cancer in Asian families, significant geographical dispersal of families and the lack of robust cancer registries [12,14]. There is currently no data in any Asian cohort to determine whether this underestimation of number of carrier families also applies to other genes.…”
Section: Introductionmentioning
confidence: 99%
“…First, while many research participants are afraid of the risks of genetic discrimination through participation in genetics research (Hamvas et al, 2004), most East Asian countries do not have legal safeguards against genetic discrimination (Joly et al, 2010; Yoon et al, 2011; Otlowski et al, 2012). However, as in the case of a Japanese genetic cohort study (Matsui et al, 2008), most research participants may wish to have future disclosure of individual risks.…”
Section: Comparative Analysismentioning
confidence: 99%